Coding games in Python - Vorderman, Carol; Steele, Craig (Digital skills consultant); Quigley, Claire; McCafferty, Daniel; Goodfellow, Martin (New York, New York : DK Publishing, 2018)
Presents an introduction to the Python programming language with illustrated steps for creating games, including puzzles, quizzes, and strategy games.--
"A step-by-step visualguide to creating your own Python games"--Cover.
Includes index.
Keywords: Python (Computer program language) -- Juvenile literature; Scripting languages (Computer science) -- Juvenile literature; Python (Computer program language); Scripting languages (Computer science); Python (Computer program language); Scripting languages (Computer science); Video games -- Programming; Python (Computer program language); Scripting languages (Computer science); Juvenile works